using Plots, ComplexPhasePortrait, ApproxFun, SingularIntegralEquations,SpecialFunctions, OscillatoryIntegrals
gr();
Dr Sheehan Olver
We can now employ the Wiener–Hopf method to solve λu(x)+∫∞0K(x−t)u(t)dt=f(x)for0<x<∞.
The Wiener–Hopf method consists of the following steps:
We will demonstrate these four steps using the example K(x)=e−|x| and f(x)=e−x.
We have ˆK(s)=∫0−∞ete−istdt+∫∞0e−te−istdt=11−is−1−1−is=21+s2
We thus have the RH problem: Φ+(s)⏟^pL(s)−g(s)⏟1+ˆK(s)Φ−(s)⏟^uR(s)=h(s)⏟−^fR(s)andlimΦ(z)=0
Here we confirm our calculations are correct for the Fourier transforms:
t = Fun(0.0 .. 40)
f = exp(-t)
fourier(f, -2.0), im/(im-2.0)
(0.19999999999999996 - 0.4000000000000001im, 0.2 - 0.4im)
1-(fourier(-exp(-t), -2.0) + fourier(-exp(Fun(-40 .. 0)), -2.0)), (2.0^2 + 3)/(2.0^2+1)
(1.4 - 4.996003610813204e-16im, 1.4)
Last lecture we employed the "guess and check" kernel factorization method to find g(s)=3+s21+s2=s+i√3s+i⏟κ+(s)s−i√3s−i⏟κ−(s)−1
Here we confirm that we have the right jump:
κ = z -> imag(z) > 0 ? (z+im*sqrt(3))/(z+im) :
(z-im)/(z-im*sqrt(3))
κ(0.1+eps()im) - κ(0.1-eps()im)*(3+0.1^2)/(1+0.1^2)
-2.220446049250313e-16 - 4.163336342344337e-17im
Writing Φ(z)=κ(z)Y(z) we have Φ+(s)−g(s)Φ−(s)=κ+(s)(Y+(s)−Y−(s))
Y = z -> imag(z) > 0 ? -im*(1-sqrt(3))/(1+sqrt(3))/(z+im*sqrt(3)) :
-2im/((z-im)*(1+sqrt(3)))
s = 0.1
Y(s+eps()im) - Y(s-eps()im)
-0.5706161966689216 + 0.08138224450306746im
im/(s-im)*(s+im)/(s + im*sqrt(3))
-0.5706161966689216 + 0.08138224450306748im
Thus we get Φ(z)=κ(z)CR[hκ+](z)={−i1+√31−√3z+iℑz>0−2i1+√31z−√3iℑz<0
We can confirm it satisfies the right RHP:
φ = z -> imag(z) > 0 ? -im*(1-sqrt(3))/(1+sqrt(3))/(z+im) :
-2im/((z-sqrt(3)*im)*(1+sqrt(3)))
g = s -> (s^2+3)/(s^2+1)
s = 0.1
φ(s+eps()im) - φ(s-eps()im)*g(s) - im/(s-im)
1.1102230246251565e-16 - 2.7755575615628914e-17im
In particular, we have ^uR(s)=Φ−(s)=κ−(s)Y−(s)=−2i(1+√3)(s−i√3)
Did this work? Amazingly, yes (and only took me four tries to get the sign right! 🕺): u(x)+∫∞0K(t−x)u(t)dt=21+√3(e−√3x+∫x0et−xe−√3tdt+∫∞xex−te−√3tdt)=21+√3(e−√3x+e−x∫x0e(1−√3)tdt+ex∫∞xe−(1+√3)tdt)=21+√3(e−√3x+11−√3(e−√3x−e−x)+e−√3x1+√3)=e−x+2e−√3x1+√3(−2−2+1+√3−2+1−√3−2)=e−x
We can verify it numerically:
t = Fun(0 .. 10)
u = 2exp(-sqrt(3)*t)/(1+sqrt(3))
x = 0.1
u(x) + sum(exp(-abs(t-x))*u) - exp(-x)
-4.036770917537069e-13